2022
DOI: 10.3389/fnut.2022.917349
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Comparison of Different Selenium Supplements: Mitigation of Heat Stress and Exercise Fatigue-Induced Liver Injury

Abstract: This study aimed to compare the protective effects of different selenium supplements against heat stress and exercise fatigue-induced liver injury and to investigate the potential mechanisms of action. Selenium-enriched soybean protein (SePro), selenium-enriched soybean peptides (SePPs), and selenomethionine (SeMet) are organic selenium supplements in which selenium replaces the sulfur in their sulfur-containing amino acids. Common peptides (PPs) are obtained by enzymatic hydrolysis of soybean protein which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…A comprehensive analysis of these indicators revealed that F3 had the most significant effect in enhancing the cellular antioxidant system and inhibiting the inflammatory response. Since the antioxidant and anti-inflammatory properties of SePPs were confirmed in our previous study, 9 here we concluded that the peptide contained in F3 is the main contributing peptide to the antioxidant and anti-inflammatory behavior of SePPs and selected this fraction for further amino acid sequence analysis.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…A comprehensive analysis of these indicators revealed that F3 had the most significant effect in enhancing the cellular antioxidant system and inhibiting the inflammatory response. Since the antioxidant and anti-inflammatory properties of SePPs were confirmed in our previous study, 9 here we concluded that the peptide contained in F3 is the main contributing peptide to the antioxidant and anti-inflammatory behavior of SePPs and selected this fraction for further amino acid sequence analysis.…”
Section: Resultssupporting
confidence: 64%
“…SePPs were obtained from selenium-enriched soybeans after crushing, defatting, alkaline acid deposition, enzymatic digestion and ultrafiltration. 9 In the process of alkaline solubilization and acid deposition, the proteins are separated by acid-base washing and are dialyzed so that small molecules (including inorganic selenium that is not attached to the proteins) are lost, so that the remaining selenium is in the form of organic selenium in SePPs.…”
Section: Preparation Of Seppsmentioning
confidence: 99%
“…Low-grade inflammation resulting from reduced cellular energy availability, and an imbalance in energy expenditure induces fatigue [ 41 , 42 ]. Anti-inflammatory diets and supplements, such as whole grains, vegetables, selenium, and omega-3 fatty acids, can alleviate physical and cognitive fatigue [ 43 , 44 ]. Similarly, EPPH administration prevented an increase in inflammation and oxidative stress due to exhaustive exercise, thus contributing to reducing exercise-induced fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al found that selenium-enriched soybean protein and its enzymatic products enhanced CAT, SOD, and GPx activity in the serum, inhibited IL-1β, IL-6, and TNF-α secretion, and p-IκB and p65 protein expression in the liver of exertional heatstroke rats, while ameliorating the hepatocyte necrosis and tissue sparing caused by heat stress. 98 Malyar et al reported that selenium-enriched probiotics reduced ALT and AST levels in the serum, enhanced SOD and GPx activity, decreased IL-6, TNF-α, and NF-κB expression levels in the liver, and prevented liver sinusoidal dilatation and venous congestion. 99 These results suggest that selenium-enriched soy protein and probiotics protect rats from heat stress-induced oxidative stress, inflammation, and liver tissue damage.…”
Section: Nutritional Interventions To Mitigate Heat Stressmentioning
confidence: 99%